2006
DOI: 10.1017/s1047951105002118
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the severity of disease and social disadvantage on quality of life in families with congenital cardiac disease

Abstract: Programmes providing psychosocial support for children with cardiac disease and their caregivers should consider risk factors which are both medical and social.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
43
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 31 publications
5
43
1
Order By: Relevance
“…In our analysis, 6–17 year‐olds with CHD whose caregiver reported financial problems were twice as likely to report a family member need for mental health services as those without family financial problems. In other studies, financial and socioeconomic stressors explain more variation in the psychological impact on families than CHD severity …”
Section: Discussionmentioning
confidence: 82%
“…In our analysis, 6–17 year‐olds with CHD whose caregiver reported financial problems were twice as likely to report a family member need for mental health services as those without family financial problems. In other studies, financial and socioeconomic stressors explain more variation in the psychological impact on families than CHD severity …”
Section: Discussionmentioning
confidence: 82%
“…Some authors state that the severity of the CHD does not affect HRQOL [4,5] while others state that there is a connection between the severity of the CHD and HRQOL [6,7]. Spurkland et al [8] found that adolescents aged between 13 and 18 years with severe CHD had a higher level of psychological problems related to physical symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported that poorer QOL is related to cardiac instability [15], greater disease severity [8,12], and poorer motor functioning and autonomy [11], although no differences were found for the variables of gender, age, and marital status [15]. Some studies have found poorer psychological wellbeing and QOL in CHD patients than in healthy control subjects [18,19], whereas others have claimed there is no difference between the two groups.…”
mentioning
confidence: 99%